E0283 Research on the relationship of anxiety symptoms to the quality of life in patients with acute coronary syndrome. (17th November 2010) - Guanghui, Liu; Wenlin, Ma; Xianzheng, Wu; Chenting, Zhu; Juping, Pan; Gang, Guo; Dayi, Hu
Abstract : Objective: Anxiety is thought to be a common symptom in patient s who suffer from acute coronary syndrome (ACS). This study aims to present a general data about the anxiety symptoms in Chinese ACS patients, and evaluate the impact of anxiety symptoms on their quality of life (QOL). Method: We enrolled 454 Chinese patient s with ACS from ShangHai, whose baseline data were obtained within 1 week after hospital admission. The subscale of Chinese version of the Hospital Anxiety and Depression Scale (HADS-A) and SF-36 were used to assess anxiety and their QOL, respectively. All the participant s were divided into 2 main groups: HADa ≥6 (n=247) and HADa 0.05). The participants from non-anxiety group had a better QOL than anxiety group (p<0.01). And anxiety was negatively associated with the QOL (p<0.01). Logistic regression analysis didn't suggest inflammatory factor is an important risk factor for anxiety of ACS patients. Conclusion: The study confirmed the western notion that anxiety is a common psychosocial problem, which also applies to Chinese patient s diagnosed with ACS. Anxious ACS patients have rather worse quality of life.